2020
DOI: 10.3389/fimmu.2020.608167
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sensitization of Malignant B Cells Through Venetoclax Significantly Improves the Cytotoxic Efficacy of CD19.CAR-T Cells

Abstract: Chimeric antigen receptor (CAR) T cell therapy has shown promising responses in patients with refractory or relapsed aggressive B-cell malignancies that are resistant to conventional chemotherapy or stem cell transplantation. A potentially combinatorial therapeutic strategy may be the inhibition of anti-apoptotic Bcl-2 family proteins, overexpressed in most cancer cells. In this study we investigated the combination of 3rd-generation CD19.CAR-T cells and the BH3 mimetics venetoclax, a Bcl-2 inhibitor, or S6384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
0
27
1
Order By: Relevance
“…Thereby, we provide the first report showing that BH3 mimetics may synergize with NK cell-based immunotherapy. In a similar approach, it has recently been shown that the BH3 mimetics ABT-737, ABT-199, and S63845 synergized with CAR-T cells to kill malignant B cells [ 47 , 48 ]. Our study demonstrates that BH3 mimetics may synergize with allogeneic activated NK cells to kill solid tumor spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we provide the first report showing that BH3 mimetics may synergize with NK cell-based immunotherapy. In a similar approach, it has recently been shown that the BH3 mimetics ABT-737, ABT-199, and S63845 synergized with CAR-T cells to kill malignant B cells [ 47 , 48 ]. Our study demonstrates that BH3 mimetics may synergize with allogeneic activated NK cells to kill solid tumor spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…The other hub genes were associated with the function of immune, differentiation, proliferation, survival, and apoptosis. Combing with the results of GO and KEGG enrichment, the function of hub genes was centered around B cell function ( Hu et al, 2018 ; Gazon et al, 2018 ; Karin and Razon, 2018 ; Tokunaga et al, 2018 ; Xiao et al, 2019 ; Huang et al, 2020 ; Yang et al, 2020 ). Considering fold change of qPCR was easier to detect in practical production and the gene function of B cell receptor signal pathway, SMC3 , JUN and CXCL10 could be suggested as molecular markers in transportation stress.…”
Section: Discussionmentioning
confidence: 99%
“…In a coculture model containing B-ALL and CD19 CAR T cells, Bcl-2 inhibition decreased the apoptosis threshold in leukemic cells leading to an enhanced CAR T cell cytotoxicity [ 86 ]. Moreover, in vitro pre-sensitization of B-ALL cells with the Bcl-2 inhibitor venetoclax resulted in an enhanced CAR T cell mediated cytotoxicity by upregulating the CD19 expression and pro-apoptotic proteins [ 87 ]. However, these strategies are yet to be tested in clinic.…”
Section: Resistance To Immune Killingmentioning
confidence: 99%